Ketidakadilan Gender dalam Cerpen Perempuan dalam Pelukan karya Tenni Purwanti - KanthiWilujeng EenNurhasanah SlametTriyadi (Universitas Muhammadiyah Tapanuli Selatan, 2021)
This research is conducted to grasp the gender inequality experience by female character in Perempuan dalamPelukan short story by TenniPurwanti. The method used in this research is literature study in which primary data obtained from the short story Perempuan dalamPelukan by TenniPurwanti are then analyzed using feminist literatarycritism theory and presented description.It is concluded that there are 5 forms of gender inequality in this short story which conclude marginalization, subordination, stereotype, violence, and double job.